Pengaruh Kepemimpinan dalam Dunia Kependidikan - Danang Nugroho; Agis Gisna Wahyuni; Ahsan Fathoni; Fayad Zabihullah; Irma Amelia; Irma Nurjanah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Although administration is a unique and sophisticated aspect of social interaction, anyone who is involved in an organization that affects others will exhibit specialized conduct. Without a doubt, each human body have the potential or aptitude to act as a controller, effectively energizing the individual to be able to lead themselves. Although the pioneer is the person with the greatest potential for influence, the term